(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A through study was conducted on the basking behaviour of some nymphalid butterflies in the fields of Bhawal national park, Rema-Kalenga, Zoological and Botanical Gardens of the University of Dhaka. The time budget and the wing-posture activities of butterflies during basking period were studied butterfly species under the family Nymphalidae. The experimental species were Junonia atlites, J. almana, J. iphita, Neptis soma, Labadea martha, Ergolis ariadne, Phalantha phalantha, Hypolimnas bolina and Athyma perius. Different types of wing postures (viz. appressed, horizontal, angled and closed type) were also recorded. It is found that butterflies take more time for their basking during winter season. Most of them prefer the month of November and December for their basking. The observations reveal that thermal basking increases the temperature in the butterfly body. It directly implies how thermoregulation associated with behavioural activities in different abiotic conditions. The results also showed the importance of wing postures for thermoregulation. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 63-72